Book Reviews (The ecumenical review, 1962)
Book reviewed in this article: THE PLACE OF THE MINISTRY IN THE CHURCH: Church Order in the New Testament, by Eduard Schweizer THE PLACE OF THE MINISTRY IN THE CHURCH: The Pioneer Ministry by Anthony T. Hanson THE PLACE OF THE MINISTRY IN THE CHURCH: The Church in the Thought of Jesus by Joseph S. Clower Jr THE ECUMENICAL MOVEMENT: PAST, PRESENT, FUTURE: On the Road to Christian Unity THE ECUMENICAL MOVEMENT: PAST, PRESENT, FUTURE: The Ecumenical Movement. What it is and what it does, by Norman Goodall THE ECUMENICAL MOVEMENT: PAST, PRESENT, FUTURE: The Hard Facts of Unity. A layman looks at the ecumenical movement, by John Lawrence THE ECUMENICAL MOVEMENT: PAST, PRESENT, FUTURE: Is Christ Divided? A Plea for Christian Unity in a Revolutionary Age, by Lesslie Newbigin THE ECUMENICAL MOVEMENT: PAST, PRESENT, FUTURE: Petite Histoire du Mouvement Oecuménique, by George Tavard THE ECUMENICAL MOVEMENT: PAST, PRESENT, FUTURE: Order, Goodness, Glory, by W. A. Whitehouse CHRISTIANS AND JEWS: The Way of Israel, Biblical Faith and Ethics, by James Muilenburg CHRISTIANS AND JEWS: Solidarität mit den Sündern. Wesen und Auftrag der Gemeinde nach dem Ephesierbrief, by Markus Barth CHRISTIANS AND JEWS: Paul: The Theology of the Apostle in the Light of Jewish Religious History, by H. J. Paul Schoeps CHRISTIANS AND JEWS: Exclusiveness and Tolerance. Studies in Jewish-Gentile relations in medieval and modern times, by Jacob Katz CHRISTIANS IN MODERN INDUSTRIAL SOCIETY: An Introduction to Religious Sociology, by F. Boulard CHRISTIANS IN MODERN INDUSTRIAL SOCIETY: The Religious Factor, by Gerhard Lenski CHRISTIANS IN MODERN INDUSTRIAL SOCIETY: Christians in an Industrial Society, by Richard Taylor CHRISTIANS IN MODERN INDUSTRIAL SOCIETY: God and the Rich Society, by D. L. Munby CHRISTIANS IN MODERN INDUSTRIAL SOCIETY: Equality and Excellence, edited by Daniel Jenkins